Tailoring the Electronic Structure and Properties of Graphdiyne by Cyano Groups - Gao, Lei; Wang, Shuailong; Wang, Fan; Yang, Ze; Li, Xiaodong; Gao, Jingchi; Fazzi, Daniele; Ye, Xiang; Wang, Xuebin; Huang, Changshui (ACS nano, 2024)
Two-dimensional (2D) materials, such as 2D carbon-based systems, have been recently the subject of intense studies, thanks to their optoelectronic properties and promising electronic performances. 2D carbon-based materials such as graphdiyne (GDY) represent an optimal platform for tuning the optoelectronic properties via precise chemical functionalization. Here, we report a synthetic strategy to precisely introduce cyano groups into the 2D GDY backbone in order to tune the electronic properties of GDY. Three kinds of cyano-modified GDY have been synthesized, namely, bearing one cyano group (CNGDY), two CN in meta (m-CNGDY), and two in para (p-CNGDY) positions. A variety of experimental data as well as first-principles calculations allowed us to elucidate the role of the cyano groups in tuning the structural and functional properties of GDYs. We found that an increase in the number of cyano groups reduces the interlayer spacing between GDY layers, increases the lithium adsorption amount, as well as impacts the lithium diffusion rate, while changes in meta- or para-position impact the energy band gap.